2018
DOI: 10.1002/ijgo.12461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with postpartum depression in women from single‐child families

Abstract: The development of PPD in women from single-child families is an important public health concern. Health practitioners should offer psychoeducation and culturally sensitive counseling during the postpartum period, and the screening of mood disorders from the prenatal to the postpartum period should be covered by maternity insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…A study in Turkey shows that there was a signi cant relationship between monthly income and depression, which was similar to the results of the present study 63 . In addition, previous studies have shown that social support was a protective factor against postpartum depression, and as far as mothers were concerned, the greatest social support comes from their husbands. Xiong et al 64 suggested that puerperae with spousal support were much less likely to develop postpartum depression. A Chinese study also con rmed that high levels of social support can reduce the risk of postpartum depression, with other factors were xed 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in Turkey shows that there was a signi cant relationship between monthly income and depression, which was similar to the results of the present study 63 . In addition, previous studies have shown that social support was a protective factor against postpartum depression, and as far as mothers were concerned, the greatest social support comes from their husbands. Xiong et al 64 suggested that puerperae with spousal support were much less likely to develop postpartum depression. A Chinese study also con rmed that high levels of social support can reduce the risk of postpartum depression, with other factors were xed 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The Postpartum Depression Factors Inventory consisted of items used to determine the different variables associated with PPD, depression, awareness of PPD, and the use of and evaluation of PPD services. It was formulated based on related studies, related literature findings, and a series of readings made by the researchers . The tool included sections on sociodemographic variables of the respondents, pregnancy‐related factors, marital relationship variables, and psychosocial aspects of the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have identified risk factors attributed to PPD among women, which were divided into the following four categories: individual factors, husband/marital factors, pregnancy‐related factors, and psychosocial factors …”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the violence sometimes suffered by children was also becoming recognised at this time, especially through the works of A. Tardieu, professor of forensic medicine in Paris, who first described the 'beaten child syndrome'. 3 In 1945, following the Second World War, a nationwide community-based mother and child protection service was established. This initiative, Protection Maternelle et Infantile (P.M.I.)…”
Section: Thematic Papermentioning
confidence: 99%